Peasant revolution in Ethiopia the Tigray People's Liberation Front, 1975-1991 - Young, John 1951- (Cambridge University Press, 1997)
In the wake of the overthrow of the Haile-Selassie regime in Ethiopia in 1974 and the coming to power of the military, a number of opposition forces launched insurrections. But only one movement, the Tigray People's Liberation Front (TPLF) triumphed, liberating Tigray in 1989, and in an ethnic-based coalition which it dominated, assuming state power in 1991. This is the first chronicle of the history of that struggle, and it is based largely on interviews with peasants who formed the core of the Tigrayan revolution and the TPLF leadership. It provides the necessary background to understanding post-1991 political developments in Ethiopia. It also offers an explanation of peasant-based revolution that contrasts with contemporary approaches by Marxists, Skocpol, and in particular the works of Wolf, Paige and Scott, all of whom largely ignore the political considerations and the role of the revolutionary party, which Dr Young identifies as a critical element in his study
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Hezbāwi wayāne ḥārenet Tegrāy / History; Tigray People's Liberation Front; Geschichte 1900-2000; Geschichte 1975-1985; Geschichte 1975-1991; Geschichte; Politik; Peasant uprisings / Ethiopia / Tigray Kifle Hāger / History / 20th century; Bauernaufstand; Äthiopischer Bürgerkrieg; Tigray Kifle Hāger (Ethiopia) / Politics and government; Provinz Tigre